Contributions from incumbent police officer’s physical activity and body composition to occupational assessment performance - Dicks, Nathan D.; Shoemaker, Marni E.; DeShaw, Kathryn J.; Carper, Michael J.; Hackney, Kyle J.; Barry, Allison M. (Frontiers in Public Health, 2023)
Police officers must perform various tasks in unpredictable work environments and potentially volatile situations. This study aimed to determine if cardiovascular fitness, body composition, and physical activity levels could predict performance in a Midwest Police Department’s Physical Readiness Assessment (PRA). Researchers collected data from thirty incumbent police officers (33.9 ± 8.3 years, female = 5). Anthropometric data included height, body mass, body fat percentage (BF%), fat-free mass (FFM), and maximal hand grip strength. The police officers also completed a physical activity rating (PA-R) scale to estimate maximal oxygen consumption (V ̇O2max) and the International Physical Activity Questionnaire (IPAQ). Police officers then conducted their department’s PRA. Stepwise linear regression analyses were used to determine the relationship between predictor variables and PRA performance. Pearson’s Product-Moment Correlations investigated relationships between anthropometric, physical fitness, and physical activity variables and PRA performance using SPSS (v.28). The significance level was set at p<0.05. Descriptive data for the sample includes BF%: 27.85 ± 7.57%, FFM: 65.73 ± 10.72 kg, hand grip strength: 55.51 ± 11.07 kg, Weekday Sedentary Time (WST): 328 ± 28.26 mins, Weekend Day Sedentary Time (WDST): 310 ± 28.92 mins, daily moderate-to-vigorous physical activity (MVPA): 29.02 ± 39.41 mins, PRA: 273.6 ± 51.4 sec and estimated V ̇O2max: 43.26 ± 6.35 ml∙kg-1∙min-1. The stepwise regression analyses indicated that BF% was predictive of PRA time (R2 = 0.32, p < 0.01); estimated V ̇O2max predictive of PRA time (R2 = 0.45, p<0.001). There were significant correlations between BF % and PRA time (r=0.57, p<0.001), PA-R and MVPA (r = 0.71, p<0.001), %BF % and WDST (r= -0.606, p<0.001), hand grip and FFM (r = 0.602, p<0.001) and PA-R and PRA time (r = -0.36, p<0.05). The results of this exploratory study highlight that higher estimated V ̇O2max and lower BF% were the best predictors for faster PRA completion times, accounting for 45% and 32% of the variance, respectively. The findings of this study support the need for wellness and fitness initiatives in law enforcement agencies focused on increasing cardiovascular fitness and physical activity while decreasing BF% to ensure optimal performance in policing and overall health.